Prediction of temperature and crystal growth evolution during 3D printing of polymeric materials via extrusion. (November 2020) - Yuan, Y.; Abeykoon, C.; Mirihanage, W.; Fernando, A.; Kao, Yue-Che; Harings, J.A.W.
Abstract: Material Extrusion (ME), which is a type of Additive Manufacturing (AM), has become widely popular in the manufacturing world. However, the evolution of a material's temperature in this relatively new manufacturing method, which plays an important role in the polymer crystallinity, is not yet well researched. Next to voids, interlayer adhesion and surface roughness, the degree of crystallinity strongly determines the quality of printed products. Hence, a thorough and deep understanding of crystallinity in ME is essential for the improvement of the parts printed. In this paper, a primary generic model is proposed to predict the temperature evolution and crystal growth of printed polymer materials. The temperature evolution was developed based on the two-dimensional domain discretisation method and the crystal growth was simulated via the Hoffman-Lauritzen theory. In the simulation, key parameters have been taken into consideration, such as the printing speed, thermal convection coefficient, thermal contact conductance with the platform, nozzle diameter and latent heat in crystallisation. Then, a single-line printing scenario was tested to verify the accuracy of the model. A comparison of the model predictions with the experimental results showed only of up to 3.8 °C deviations which is a 2% of maximum percentage mismatch from the full scale reading. Graphical abstract: Unlabelled Image Highlights: A novel generic model to simulate the temperature evolution and crystal growth rate during material extrusion was proposed. Effects of major process parameters during material extrusion additive manufacturing are considered in the proposed model. The proposed novel model can predict the temperature evolution precisely and the relative prediction error is less than 2%. The proposed method should be useful for setting-up and optimizing of additive manufacturing and polymer extrusion processes.